A case of canine epitheliotropic lymphoma (mycosis fungoides) - SARIDOMICHELAKIS (Μ. Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M. N.; KOUTINAS (X.K. ΚΟΥΤΙΝΑΣ) C. K.; KOUTINAS (Α. Φ. ΚΟΥΤΙΝΑΣ) A. F. (Journal of the Hellenic Veterinary Medical Society, 2018)
The clinical picture, diagnosis and treatment of a dog with epitheliotropic lymphoma are presented. The dog (male, mongrel, 13-year old) was admitted to our Clinic with a 5-month history of non-pruritic skin lesions. At clinical examination a multifocal to diffuse exfoliative erythrodermia was the most striking finding. Diagnosis of epitheliotropic lymphoma was based on cutaneous histopathology, revealing a dense dermal and epidermal lymphocytic infiltration and Pautrie microabcess formation. Initial treatment with isotretinoin had a poor impact on skin lesions that progressed to the macular stage. On the contrary, combination chemotherapy with Lasparaginase and isotretinoin resulted in substantial improvement. The animal died, following a short period of depression and inappetance, 15 months after the first appearance of skin lesions and 10 months after diagnosis.